2006
DOI: 10.1097/01.aog.0000227786.69257.a8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Among Apical Support, Levator Ani Impairment, and Anterior Vaginal Wall Prolapse

Abstract: These results suggest that a prolapse can develop as a result of impairment of the muscular and apical supports of the anterior vaginal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
98
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 25 publications
(15 reference statements)
7
98
0
11
Order By: Relevance
“…Indications for pessary therapy can include patient preference for conservative treatment, temporary family planning when the patient intends to have more children, and an increased risk of perioperative complications due to co-morbidities [65]. Prolapse of the anterior vaginal wall is commonly associated with an apical defect, so that surgical repair of the middle compartment should be considered in these patients [66]. Success rates for anterior vaginal wall repair were reported in 22 randomized studies; they varied strongly and also depended on the additional surgical procedures carried out concomitantly.…”
Section: Pessary Therapymentioning
confidence: 99%
“…Indications for pessary therapy can include patient preference for conservative treatment, temporary family planning when the patient intends to have more children, and an increased risk of perioperative complications due to co-morbidities [65]. Prolapse of the anterior vaginal wall is commonly associated with an apical defect, so that surgical repair of the middle compartment should be considered in these patients [66]. Success rates for anterior vaginal wall repair were reported in 22 randomized studies; they varied strongly and also depended on the additional surgical procedures carried out concomitantly.…”
Section: Pessary Therapymentioning
confidence: 99%
“…Finite element (FE) method is a non-invasive and repetitive numerical simulation method which makes it effective for this kind of studies. Chen et al [7] established a two-dimensional (2D) biomechanical model of the anterior vaginal wall and its support system. The results showed that if the pubovisceral impairment reached at a certain level, the anterior vaginal wall would prolapse; at 60% pubovisceral muscle impairment, a 90% impairment of apical support caused the prolapse to increase from 0.3 to 1.9 cm.…”
mentioning
confidence: 99%
“…The anterior vaginal wall was usually modeled as a separated part from the posterior compartment, which was entirely made up of the posterior vaginal wall and rectum. In addition, the ligaments were simulated by passive elastic springs [7] or 3D truss elements [8]. The oversimplification made it impossible to evaluate the shear stress in the lateral vaginal walls, which is, however, eagerly needed clinically.…”
mentioning
confidence: 99%
See 2 more Smart Citations